Surface of Alumina Films after Prolonged Breakdowns in Galvanostatic Anodization - Christian Girginov; Stephan Kozhukharov (International Journal of Electrochemistry)
Breakdown phenomena are investigated at continuous isothermal (20∘C) and galvanostatic (0.2–5 mA cm−2) anodizing of aluminum in ammonium salicylate in dimethylformamide (1 M AS/DMF) electrolyte. From the kinetic 𝑈𝑡(𝑡)-curves, the breakdown voltage (𝑈𝐵) values are estimated, as well as the frequency and amplitude of oscillations of formation voltage (𝑈𝑓) at different current densities. The surface of the aluminum specimens was studied using atomic force microscopy (AFM). Data on topography and surface roughness parameters of the electrode after electric breakdowns are obtained as a function of anodization time. The electrode surface of anodic films, formed with different current densities until the same charge density has passed (2.5 C cm−2), was assessed. Results are discussed on the basis of perceptions of avalanche mechanism of the breakdown phenomena, due to the injection of electrons and their multiplication in the volume of the film.